ANALISIS HUBUNGAN KARAKTERISTIK ANTARA VOLUME, KECEPATAN, DAN KEPADATAN ARUS LALU LINTAS DENGAN MENGGUNAKAN MODEL UNDERWOOD (Studi Kasus: Jalan Raya Kletek, Kabupaten Sidoarjo) - Muhammad Yusuf Ramadhan; Hendrata Wibisana (Racic : Rab Construction Research, 2024)
Jalan Raya Kletek is one of the roads known as a T-junction (junction three) that connects Surabaya-Sidoarjo city and Surabaya-Madiun. This road is included in the 4/2D lane type. One of the problems that often occurs here is traffic congestion, due to economic growth and vehicle ownership which is the cause. Seeing traffic conditions like this, it is necessary to analyze traffic characteristics referring to three main parameters, namely, volume, speed and density. One of the models that will be used to carry out this analysis is the Underwood model. From the results of the analysis carried out on Jalan Raya Kletek, it was found that the largest R2 value was on Friday Segment 1 Line 2 (Surabaya direction) with a value of 0.79. The values ​​for each variable obtained in this segment are, Qmax of 3099.35 pcu/hour, Vf of 36.57 km/hour, Vm of 13.45 km/hour and Dm of 230.41 pcu/km. Because the largest R2 value is close to +1, it can be concluded that this segment on Jalan Raya Kletek is close to the results of actual field conditions.